2023
DOI: 10.14581/jer.23001
|View full text |Cite|
|
Sign up to set email alerts
|

Brain Glutathione Increase and Seizure Burden Decrease in Patients with Intractable Epilepsy on Ketogenic Diet

Abstract: Background and Purpose: Ketogenic diet (KD) improves seizure control in patients with drug-resistant epilepsy. As increased mitochondrial levels of glutathione (GSH) might contribute to a change in seizure susceptibility, we quantified changes of absolute GSH levels in the brain by in vivo 1H magnetic resonance spectroscopy (1H MRS) and correlate that with degree of seizure control in patients on KD.Methods: Five cognitively normal adult patients with drug-resistant epilepsy were initially included and 2 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Glutathione (GSH), abundant in the brain, is crucial in maintaining redox homeostasis in the CNS through antioxidant activity. Studies of epilepsy patients on KD have demonstrated higher levels of brain GSH in response to the diet [ 168 , 169 ]. Other ketone bodies including acetone, βHB and acetoacetate can also be measured by MRS in future applications.…”
Section: Emerging Nutritional Interventions To Promote Early Brain Re...mentioning
confidence: 99%
“…Glutathione (GSH), abundant in the brain, is crucial in maintaining redox homeostasis in the CNS through antioxidant activity. Studies of epilepsy patients on KD have demonstrated higher levels of brain GSH in response to the diet [ 168 , 169 ]. Other ketone bodies including acetone, βHB and acetoacetate can also be measured by MRS in future applications.…”
Section: Emerging Nutritional Interventions To Promote Early Brain Re...mentioning
confidence: 99%